The research of suicidal behaviour in alcohol dependence - Mırsal, Hasan; Pektaş, Özkan; Kalyoncu, Ayhan; Mırsal, Nursel (Journal of Dependence, 2001)
The prevalence of suicide attempts is %10-15 in alcohol related disorders. On the other hand the existence of alcohol use in suicide attempts is in higher rates. The factors which increase the sucide risks in alcohol related disorders are accompanying major depressive disorder, physical illness, insufficient psychosocial support, living alone and unemployment (1,2). The aim of this study is to investigate the causes of suicide behaviour retrospectively. The 25 participant subjects of the study were the patients hospitalized into our clinic between December 1998 and March 1999- After a drug free observation period fallowing the detoxification treatment, a semistructured interview form, suicide scales, Hamiton depression scale, state-trait anxiety inventoiy were used to evaluate the patients. Ninety-six percent of patients (n=24) were male and 4% (n=l ) was female. The average age of patients were 40.4 (sd=5-D, the average starting age to use alcohol were 18.8 (sd=4.7), and the average time in which the patients felt the problems related with alcohol were 8.8 (sd=4.8) years. Five subjects (20%) had the suicide behaviour and/or serious suicide thoughts in the last year.Alt- hough there is not a statistically significant difference between two groups for state-trait anxiety inventory) F=0.01, p> 0.05), the differences in evalution of Hamiton Depression Scales was statistically significant (F= 15.3, p<0.001). The rate of alcohol dependence in family is higher in the group which have suicide thought/behaviour. The results of the study show that patients with alcohol dependence may have different sociodemographical and clinical properties.